A three-country comparison of psychotropic medication prevalence in youth - Gardner James F; Fegert Joerg M; Janhsen Katrin; Berg Lolkje; Safer Daniel J; Zito Julie M; Glaeske Gerd; Valluri Satish C (BMC, 2008)
Abstract Background The study aims to compare cross-national prevalence of psychotropic medication use in youth. Methods A population-based analysis of psychotropic medication use based on administrative claims data for the year 2000 was undertaken for insured enrollees from 3 countries in relation to age group (0-4, 5-9, 10-14, and 15-19), gender, drug subclass pattern and concomitant use. The data include insured youth aged 0-19 in the year 2000 from the Netherlands (n = 110,944), Germany (n = 356,520) and the United States (n = 127,157). Results The annual prevalence of any psychotropic medication in youth was significantly greater in the US (6.7%) than in the Netherlands (2.9%) and in Germany (2.0%). Antidepressant and stimulant prevalence were 3 or more times greater in the US than in the Netherlands and Germany, while antipsychotic prevalence was 1.5-2.2 times greater. The atypical antipsychotic subclass represented only 5% of antipsychotic use in Germany, but 48% in the Netherlands and 66% in the US. The less commonly used drugs e.g. alpha agonists, lithium and antiparkinsonian agents generally followed the ranking of US>Dutch>German youth with very rare (less than 0.05%) use in Dutch and German youth. Though rarely used, anxiolytics were twice as common in Dutch as in US and German youth. Prescription hypnotics were half as common as anxiolytics in Dutch and US youth and were very uncommon in German youth. Concomitant drug use applied to 19.2% of US youth which was more than double the Dutch use and three times that of German youth. Conclusion Prominent differences in psychotropic medication treatment patterns exist between youth in the US and Western Europe and within Western Europe. Differences in policies regarding direct to consumer drug advertising, government regulatory restrictions, reimbursement policies, diagnostic classification systems, and cultural beliefs regarding the role of medication for emotional and behavioral treatment are likely to account for these differences.